Method for measuring X-ray reflections of microelements of inorganic compounds in soft tissues - Mikhailov, I.; Negoduyko, Volodymyr; Mikhaylusov, R.; Mikhailov, A.; Borisova, S. (My University, 2023)
An alternative method is proposed for measuring X-ray diffraction peaks from micro-impurities of inorganic phases in soft tissues. Unlike traditional XRD, each of the diffraction peaks corresponding to the interplanar spacing di , is measured using radiation with a wavelength of λi →2di . This makes it possible to register diffraction peaks at large θ angles, thereby increasing the angular resolution ∼tanθ. This approach made it possible to increase the beam angular divergence ∆θ from 0.05° (for standard XRD) to 3°, gain ∼(∆θ) 2 in the spectrometer luminosity, and reduce ∼(∆θ) -2 radiation load per unit area of soft tissue. A criterion for choosing the wavelength and beam divergence based on the micro-impurity structure is proposed. The results of measuring the diffraction peaks of micro-impurities of iron oxides in soft tissues damaged by a fragment wound are presented. The excess iron content in damaged tissues was certified by the XRF method with calibration using standard samples and did not exceed 0.4 mass%. Measurements of the main diffraction peaks of iron oxides Fe2 O3 , d=2.69Å, as well as Fe3 O4 , d=1.61Å and FeO(OH), d=1.71Å, were carried out in Cl- Кα ( . λ = 4 728 ) and Sc-Кα ( λ = 3. ) 031 , respectively. We used the scheme of a portable EDXRF spectrometer with a secondary KCl-Sc target and an angular beam divergence of ∆θ≈3°. Without radiation damage to soft tissues, the detection limits were reached: 0.12 mass% for Fe2 O3 , 0.059 mass% for Fe3 O4 and 0.034 mass% for FeO(OH)
Спосіб вимірювання рентгенівських відбиттів мікроелементів неорганічних сполук у м’яких тканинах
Keywords: X-ray diffraction; micro-impurities; soft tissues; EDXRF spectrometer; secondary target; 2023a